Mechanisms of corporate digital transformation on asymmetric capital structure adjustment—the mediating role of information asymmetry and financial stability - Jin Li; Zijian Li (Heliyon)
In the context of the digital economy, enterprises face dual challenges in optimizing their capital structure and achieving sustainable development. To address market risks caused by information asymmetry and to ensure the flexibility and adaptability of their capital structure, firms must strike a balance between short-term financial demands and long-term strategic objectives. Based on data from Chinese A-share listed companies from 2010 to 2022, this study employs a fixed-effects model and mediation analysis to systematically examine the impact of digital transformation on the dynamic adjustment of capital structure. The findings reveal that digital transformation significantly accelerates the speed of capital structure adjustment, with the interaction coefficient between the digital transformation index and the lagged capital structure term estimated at −0.0197 (p < 0.01). Among various digital technologies, big data exhibits the most pronounced effect on increasing adjustment speed, with an interaction coefficient of −0.0250 (p < 0.01). The impact of digital transformation is asymmetric: highly leveraged firms adjust their capital structures at a significantly faster rate than low-leverage firms, with interaction coefficients of −0.0257 (p < 0.01) and −0.0196 (p < 0.05), respectively. Additionally, information asymmetry and financial stability serve as critical mediators in the relationship between digital transformation and capital structure adjustment, effectively reducing financing costs and enhancing the efficiency of capital markets. Furthermore, the study highlights that the benefits of digital transformation are particularly pronounced in non-state-owned enterprises, firms with high financing constraints, and labor-intensive industries. This research advances the theoretical framework of dynamic capital structure adjustment, expands the scope of digital transformation studies, and provides actionable insights for corporate managers and policymakers in optimizing capital allocation strategies.